The quality of drinking water as a risk-factor of skin lesions among the North Daghestan population - T. O. Abdulmutalimova; G. D. Mamasheva (Медицинский вестник Юга России, 2018)
Objective: to study the epidemiological features of the spread of arsenodermatitis among the population of Northern Dagestan with the identification of populations most exposed to arsenic. Materials and methods: in the course of this study, 915 case histories of patients of the Republic Dermatovenerologic Dispensary, who have lived for more than 5 years in the territory of the hydrogeochemical anomaly, were analyzed. The study of ethnic predisposition to the development of skin pathologies was carried out on the basis of an analysis of available literature data. Results: 40.6 % of the population use artesian water with arsenic contamination 20-50 times higher than the permissible level for drinking. The prevailing localization in the analysis of the general structure of skin diseases of a noninfectious nature by study areas is the various forms of the psoriases, which were detected in half of the patients (51.6%). The spread of skin pathologies among different ethnic groups in North Dagestan did not reveal any differences. Conclusions: the clinical cases of dermatitis among the patients of the Republic Dermatovenerologic Dispensary revealed in the population are characterized by symptoms similar to those described in the literature of arsenodermatitis. To verify the data, it is necessary to conduct detailed studies using biomarkers (hair, urine) in exposed groups of the populationwith identified skin pathologies consuming water with different levels of arsenic for drinking.